2018
DOI: 10.3390/su10114317
|View full text |Cite
|
Sign up to set email alerts
|

Improving Water Use Efficiency under Deficit Irrigation in the Jordan Valley

Abstract: The Jordan Valley is the prime irrigated agricultural area in Jordan which suffers shortage of water putting severe limitation on water allocation to farmers. To alleviate the problem, deficit irrigation was proposed for some vegetables such as bell pepper. Two field experiments in two growing seasons were conducted using bell pepper (Capsicum Annuum L.) to assess the effect of deficit irrigation on yield, water use efficiency (WUE), and water productivity (WP). The treatments were three irrigation levels: 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Since ALMANAC simulated the dry yields, moisture contents were multiplied to the yields, and the results were divided by the amount of water that was transpired by the plants during the growing season. In general, the simulated WUEs were moderately close to the values in range of the measured WUE reported by [8][9][10][11][12][13] (Table 4). Among all eight vegetables, cabbage had the highest WUE, while zucchini had the lowest WUE.…”
Section: Almanac Yield and Water Use Efficiency Simulation And Validationsupporting
confidence: 83%
“…Since ALMANAC simulated the dry yields, moisture contents were multiplied to the yields, and the results were divided by the amount of water that was transpired by the plants during the growing season. In general, the simulated WUEs were moderately close to the values in range of the measured WUE reported by [8][9][10][11][12][13] (Table 4). Among all eight vegetables, cabbage had the highest WUE, while zucchini had the lowest WUE.…”
Section: Almanac Yield and Water Use Efficiency Simulation And Validationsupporting
confidence: 83%
“…It has been widely reported that, when water for irrigation is either scarce or expensive, well-managed deficit irrigation improves both water productivity and the farmer net income, as compared to full irrigation (English, 1990;Fereres and Soriano, 2007;Geerts and Raes, 2009;Ruiz-Sanchez et al, 2010;Alcon et al, 2014;Shammout et al, 2018). The farmer must identify the most suitable options for irrigation and then carry out a proper study to assess which one is the best for the orchard conditions and the chosen production target.…”
Section: The Joint Use Of Economic Indicators and Profit Functions Fomentioning
confidence: 99%
“…Among the reasons for water scarcity in Jordan are climate change [28][29][30][31][32][33][34][35], population growth [36], geopolitical location as a downstream country, and refugee influxes due to political instability in the region [37]. In Jordan, water scarcity poses serious challenges for the wellbeing, security and economic development of the country [38]. Although proper wellfield management cannot solve all complex social, environmental and economic issues related to water scarcity, it can help in reducing groundwater pumping costs, saving energy [39] and granting a more constant and reliable supply of water to the population [40].…”
Section: Introductionmentioning
confidence: 99%